Numerical Simulation of Sloshing in Different Tank shape with Vertical and Horizontal Baffle Using Smoothed Particle Hydrodynamics - Trimulyono, Andi; Adietya, Berlian Arswendo; Alvianto, Jodhy Irsyad; Chrismianto, Deddy; Syahab, Husein (Department of Naval Architecture - Diponegoro University, 2024)
Computational Fluid Dynamics (CFD) is a numerical analysis used to solve problems related to free surface flows. Two major methods have been developed in the CFD, mesh-based and meshless CFD, in this paper. The meshless CFD approach, Smoothed Particle Hydrodynamics (SPH), is employed. SPH is a meshless method where each fluid is represented by a point or particle. In this study, a 3D simulation was carried out for the phenomenon of sloshing with roll motion in prismatic, square, cylindrical and spherical tanks with a duration of sloshing of 28 seconds. The filling ratio was 25% for all tanks used in this study. Vertical and horizontal baffles were also used to suppress the sloshing. The ratio height of the vertical baffle is 0.9, and the horizontal baffle is 0.2. The results of this study show a successful comparison of dynamic pressure, free surface heights, forces, and moments in various tank variations. The installation of baffles in the tank influences the sloshing phenomenon, especially in the use of vertical baffles, where the vertical baffle is the most effective baffle used in all tanks.